The development factory unlocking the potential of process innovation - Pisano, Gary P. 1961- (Harvard Business School Press, 1997)
Pisano challenges the widely held product-process life cycle view of competition, which suggests that industries tend to emphasize either product innovation or process innovation. He also questions the notion that there is a conflict between pursuit of product innovation and pursuit of lower costs, arguing that product development and process development capabilities are complementary. Extending the lessons to a wide variety of manufacturing industries, The Development Factory will guide companies toward unlocking the potential of process development and understanding the patterns of organizational behavior and managerial actions that help create and implement new capabilities over time